2019
DOI: 10.1038/s41386-019-0578-2
|View full text |Cite
|
Sign up to set email alerts
|

Prior cocaine self-administration impairs attention signals in anterior cingulate cortex

Abstract: Although maladaptive decision-making is a defining feature of drug abuse and addiction, we have yet to ascertain how cocaine self-administration disrupts neural signals in anterior cingulate cortex (ACC), a brain region thought to contribute to attentional control. To address this issue, rats were trained on a reward-guided decision-making task; reward value was manipulated by independently varying the size of or the delay to reward over several trial blocks. Subsequently, rats self-administered either a cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 56 publications
15
38
0
Order By: Relevance
“…Altogether, these results replicate previous findings that rats demonstrate a preference for higher-valued rewards through their choices and reaction times, and that responding is biased towards high-valued rewards in animals previously exposed to cocaine (Brockett et al, 2018; Burton et al, 2018b, 2017; Vázquez et al, 2019). Interestingly, in contrast to previous studies, we found that cocaine-exposed rats were overall more accurate on forced-choice trials ( Fig .…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Altogether, these results replicate previous findings that rats demonstrate a preference for higher-valued rewards through their choices and reaction times, and that responding is biased towards high-valued rewards in animals previously exposed to cocaine (Brockett et al, 2018; Burton et al, 2018b, 2017; Vázquez et al, 2019). Interestingly, in contrast to previous studies, we found that cocaine-exposed rats were overall more accurate on forced-choice trials ( Fig .…”
Section: Resultssupporting
confidence: 88%
“…In addition to reporting these novel aspects of insula encoding in control rats, we also determined how these correlates are disrupted after chronic cocaine self-administration. Our results replicate previous behavioral findings demonstrating that rats in both cocaine and control groups prefer high-valued rewards, and that this preference is exaggerated in cocaine-exposed animals (Burton et al, 2018b, 2017; Roesch et al, 2007; Roesch and Bryden, 2011; Vázquez et al, 2019). Interestingly, prior cocaine self-administration shifted the balance of encoding in insula from cues and context to reward.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations